Pengaruh Pemberian Dosis Pupuk Hayati Mikoriza pada Pertumbuhan Bibit Dua Varietas Kelapa Sawit di Pembibitan Awal - Sodikin, Erizal; Sulaiman, Firdaus; Amar, Muhammad; Achadi, Teguh; Yakup, Yakup; Sefrila, Marlin; Apria, Apria (Politeknik Negeri Lampung, 2022)
This study aims to determine the best dose of mycorrhizal biological fertilizer for palm oil seedling growth of DxP Simalungun and DxP Sriwijaya 2 varieties in the pre-nursery stage. This research was carried out by the shade house of the Faculty of Agriculture, Sriwijaya University, Indralaya, Ogan Ilir, from October 2020 to January 2021. The study used the Completely Randomized Design method consisting of eight treatments and four replications, in which there were three plants in each experimental unit. The treatment provided consists of A (Simalungun without mycorrhizal), B (Simalungun given 5 g of mycorrhizal), C (Simalungun given 10 g of mycorrhizal), D (Simalungun given 15 g of mycorrhizal), E (Sriwijaya 2 without mycorrhizal), F (Sriwijaya 2 given 5 g of mycorrhizal), G (Sriwijaya 2 given 10 g of mycorrhizal), and H (Sriwijaya 2 was given 15 g of mycorrhizal). The results showed that the treatment of mycorrhizal biofertilizer with a dose of 5 g is the best treatment to the height of seedlings, the number of leaves, the leaf greenness index, the total leaf area, the diameter of the seedlings, the number of roots, the length of roots, and the dry weight of seedlings. The Sriwijaya 2 variety is more responsive to the provision of mycorrhizal biofertilizers.